ANALISIS MAKNA DENOTATIF PADA NOVEL MIDNIGHT DIARIES BY MALIO HARTIGAN KARYA SKYSPHIER - Indah Putri Amalia; Hilda Farida (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
This article discusses the denotative meaning in the novel Midnight Diaries by Malio Hartigan by Skysphire. Denotative meaning is an objective meaning, so the meaning is concrete according to the actual meaning. Denotative meaning is also referred to as lexical meaning, dictionary meaning, or literal meaning. Through this research, the author aims to identify how denotative meaning is used to construct important elements in the novel, such as the depiction of setting, characters, and events. This research will also explore how the literal meaning contained in the text creates a clearer and more purposeful reading experience. This research uses a descriptive qualitative method with text analysis to explore the meaning of language according to literary context. Data were collected through observation of language in the novel and identification of elements containing denotative meaning. The analysis was conducted systematically, starting from coding, context interpretation, to the presentation of findings related to the function of denotative meaning in the novel. The results of the analysis show that this novel uses denotative meaning to clarify the background of the story, describe the conflict experienced by the main character, and create a certain atmosphere that supports the storyline. Through this analysis, readers are expected to understand how denotative meaning functions in shaping the narrative and enriching the reading experience. Furthermore, the analysis shows that the use of denotative meaning helps the reader to understand the narrative. Keywords: text analysis, denotative meaning, novel